11-oxygenated androgens and their relation to hypothalamus-pituitary-gonadal-axis disturbances in adults with congenital adrenal hyperplasia. Issue 212 (September 2021) - Auer, Matthias K.; Paizoni, Luisa; Neuner, Meike; Lottspeich, Christian; Schmidt, Heinrich; Bidlingmaier, Martin; Hawley, James; Keevil, Brian; Reisch, Nicole
Highlights: 11-oxygenated androgens were significantly elevated in men with hypogonadotropic hypogonadism and women with amenorrhea. 11-ketotestosterone and 11β-hydroxyandrostenedione were negatively associated with FSH but not with LH levels in men. Elevated 11-oxygenated androgens were not associated with the presence of testicular adrenal rest tumors in men with CAH. Disproportionately elevated 11-oxygenated androgens were not more common in patients with HPG-disturbances or TART. Abstract: Context: Hypothalamus-pituitary-gonadal (HPG)-axis disturbances are a common phenomenon in patients with classic congenital adrenal hyperplasia (CAH). 11-oxygenated androgens have been suggested to play a role in this context. Design: Cross-sectional single center study including 89 patients (N = 42 men, N = 55 women) with classic CAH. Main Outcome Measures: Differences in steroid markers in men with hypogonadism and women with secondary amenorrhea with a special focus on 11-ketotestosterone (11KT) and 11β-hydroxyandrostenedione (11OHA4). Results: Hypogonadotropic hypogonadism was present in 23 % of men and 61 % of those women currently not on contraceptives suffered from irregular menstrual cycles or amenorrhea. Testicular adrenal rest tumor (TART) was documented in 28 % of men. 11KT (3.5x) and 11OHA4 (5.7x) among other adrenal steroids were significantly elevated in men with hypogonadism and in women with amenorrhea in comparison to those with a regular cycle (11KT: 5.2x; 11OHA4: 3.7x). 11-oxygenated androgens were not higher in men with TART than in those without. There was a negative association of 11KT and 11OHA4 with FSH but not with LH in men. As expected, all steroids were strongly correlated with each other and cases of disproportionally elevated 11-oxygenated androgens that could explain for HPG-disturbances or TART in otherwise controlled patients were rare and also found in eugonadal individuals. Conclusions: In CAH, 11-oxygenated androgens are elevated in women with menstrual disturbances and in men with hypogonadotropic hypogonadism. Due to the close correlation of 11-oxygenated androgens with other adrenal steroids it remains to be shown if their measurement is superior to conventional markers of androgen control.